Search for B 0→π 0π 0 decay - Asner, D; Eppich, A; Hill, T; Morrison, R; Briere, R; Chen, G; Ferguson, T; Vogel, H; Gritsan, A; Alexander, J; Baker, R; Bebek, C; et al. (2002)
We have searched for the charmless hadronic decay of B 0 mesons into two neutral pions. Using 9.13 fb -1 taken at the Y(45) with the CLEO detector, we obtain an improved upper limit for the branching fraction B(B 0 → π 0π 0)<5.7×10 -6 at the 90% confidence level. © 2002 The American Physical Society.